Alternation in Enzyme Activities to Assess the Tolerance/Susceptibility of Rice (Oryza sativa L.) Genotypes to Heat and Drought stresses - Kumar, A. R. Nirmal; Vijayalakshmi, C.; Vijayalakshmi, D. (International Journal of Bio-resource and Stress Management, 2017)
The field experiment was conducted to observe the effect of combined heat and drought stress on Catalase, Peroxidase, Nitrate reductase and Soluble protein contents to screen and study the biochemical basis of heat and drought tolerance in three rice genotypes (ADT 43, TKM 9 and N22). The stresses were imposed at panicle initiation (PI) and anthesis stages of crop growth. The genotype N22 was found to be tolerant followed by TKM 9 while ADT 43 was observed to the susceptible genotype based on the above biochemical traits. Irrespective of genotypes, anthesis stage stress brought about accumulation of antioxidant enzymes and soluble protein compared to stress at PI stage. ADT 43 recorded low catalase activity of (6.91 µg H2O2 min-1 g-1), peroxidase activity of (4.35 Δ 430 nm g-1 min-1), soluble protein content (11.05 mg g-1) and Nitrate reductase activity of (14.52 µg NO2 g-1 h-1). While, N22 recorded higher catalase activity of (7.32 µg H2O2 min-1 g-1), peroxidase activity of (5.68 Δ 430 nm g-1 min-1), soluble protein content (11.01 mg g-1) and Nitrate reductase activity of (15.84 µg NO2 g-1 h-1). Higher antioxidant enzymes activity coupled with more soluble protein and Nitrate reductase activity was clearly demonstrated in the tolerant genotype (N22) compared to susceptible genotype (ADT 43). These results confirm that these biochemical traits may be used to screen rice genotypes for combined stresses and understand the mechanism underlying stress tolerance.